(untitled) (Nepalese Journal of Radiology, 2020)
Introduction: The differentiation of rim enhancing abscess from high grade necrotic lesions is difficult in conventional imaging. Our purpose was to assess the role of diffusion weighted imaging of intracranial rim enhancing lesions to differentiate the etiologies. Methods: Fifty one patients, 32 male and 19 female with mean age of 48.47 years and with rim enhancing intracranial lesions in magnetic resonance imaging, who underwent surgery from January 2012 to December 2012, were studied for different characteristics of the lesions in DWI and pathologically correlated the observed findings. Results: Out of 58 rim enhancing lesions 21 were primary brain tumor, 18 abscess, 14 metastasis and 5 neurocysticercosis. Twenty lesions had restricted diffusion in center, 22 lesions had thin smooth enhancing rim and 23 lesions were with low T2 complete rim. Diffusion restriction at non enhancing center of the lesion and thin smooth enhancing rim have sensitivity and specificity of 88.89% and 90.24% (p <0.0001) for brain abscess and 83.33% and 80.49% (p <0.0001) for other lesions. ADC ratio of center to that of normal white matter showed sensitivity and specificity of 88.9% and 90% respectively (p <0.0001) at cut off point of 1.09. Lesions with thin smooth rim enhancement with diffusion restriction in nonenhancing center are 100% specific for brain abscess. Conclusions: On studying the different MRI characteristics of rim enhancing lesions, combining enhancement characteristic with DWI is more helpful in coming to the proper diagnosis.